2012
DOI: 10.3767/003158512x660571
|View full text |Cite
|
Sign up to set email alerts
|

New penicillin-producing <I>Penicillium</I> species and an overview of section <I>Chrysogena</I>

Abstract: Species classified in Penicillium sect. Chrysogena are primary soil-borne and the most well-known members are P. chrysogenum and P. nalgiovense. Penicillium chrysogenum has received much attention because of its role in the production on penicillin and as a contaminant of indoor environments and various food and feedstuffs. Another biotechnologically important species is P. nalgiovense, which is used as a fungal starter culture for the production of fermented meat products. Previous taxonomic studies often had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 40 publications
3
88
0
Order By: Relevance
“…The topology is consistent between these two phylograms, recognizing P. salamii as a separate species using the GCPSR (Genealogical concordance phylogenetic species recognition) concept (Dettman et al, 2003). The extrolite analysis revealed that P. salamii produces asperphenamate typical of most members of section Brevicompacta (Frisvad et al, 2013), and chrysogine (and precursors) found in members of section Chrysogena (Houbraken et al, 2012). It is interesting to note that multiple recent horizontal transfers of a large genomic region occurred in cheese making fungi (Cheeseman et al, 2014).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The topology is consistent between these two phylograms, recognizing P. salamii as a separate species using the GCPSR (Genealogical concordance phylogenetic species recognition) concept (Dettman et al, 2003). The extrolite analysis revealed that P. salamii produces asperphenamate typical of most members of section Brevicompacta (Frisvad et al, 2013), and chrysogine (and precursors) found in members of section Chrysogena (Houbraken et al, 2012). It is interesting to note that multiple recent horizontal transfers of a large genomic region occurred in cheese making fungi (Cheeseman et al, 2014).…”
Section: Discussionmentioning
confidence: 75%
“…P. astrolabium produces asperphenamate and xanthoepocin, but not chrysogine. Chrysogine is produced by members of section Chrysogena (Houbraken et al, 2012), while asperphenamate is produced by most members of section Brevicompacta (Frisvad et al, 2013) (Table 3).…”
Section: Phenotypic Characterization and Extrolite Analysismentioning
confidence: 99%
“…β-Tubulin sequences of Penicillium subgenus Penicillium section Chrysogena were aligned using neighbor-joining tree with reference sequences from Houbraken et al (2012). P. chrysogenum, Penicillium flavigenum and Penicillium rubens were differentiated.…”
Section: Mycological Analysismentioning
confidence: 99%
“…Genomic DNA was extracted using the Ultraclean™ Microbial DNA isolation kit (MoBio, Solana Beach, USA). After DNA extraction, parts of the BenA, CaM, internal transcribed spacers (ITS) and RPB2 regions were amplified, sequenced and annotated (Houbraken et al 2012;Houbraken and Samson 2011). The newly generated sequences were supplemented with sequence data from GenBank.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Three agar plugs were extracted per agar medium as described before (Houbraken et al 2012;Nielsen et al 2011). The extracts were analysed using UHPLC-DAD and compounds were identified against an internal database of UV spectra and literature.…”
Section: Extrolite Analysismentioning
confidence: 99%